2022
DOI: 10.13005/bpj/2514
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine Prevents Hepatic Steatosis in Deep-Frying Oil-Treated Rat

Abstract: Deep-frying oil is a source of free radicals that causes oxidative stress in the body and lead to chronic and degenerative diseases, including non-alcoholic fatty liver (NAFLD). Steatosis, or fatty liver, is one of NAFLD and is a common result of moderate to severe hepatocellular insult. L-Carnitine involves in the metabolism of fat and has a potential role as an antioxidant. In the present study, we aimed to elucidate the role of L-Carnitine in deep-frying oil-treated rats. We equally divided thirty-six male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In the present study, MDA and SOD were used as oxidative stress markers. MDA is produced as a byproduct of lipid peroxidation, and SOD acts as a radical scavenger by catalyzing the dismutation of the superoxide anion radical into non-reactive molecules [46,47]. Studies showed that the animal model of psychosocial stress exhibits elevated MDA levels and reduced levels of SOD in the brain tissue [48], causing the depletion of 5-HT levels and triggering anxiety- and depressive-related behaviors, as evidenced by the open field and forced swim tests.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MDA and SOD were used as oxidative stress markers. MDA is produced as a byproduct of lipid peroxidation, and SOD acts as a radical scavenger by catalyzing the dismutation of the superoxide anion radical into non-reactive molecules [46,47]. Studies showed that the animal model of psychosocial stress exhibits elevated MDA levels and reduced levels of SOD in the brain tissue [48], causing the depletion of 5-HT levels and triggering anxiety- and depressive-related behaviors, as evidenced by the open field and forced swim tests.…”
Section: Discussionmentioning
confidence: 99%